Reducing interethnic social distance among adolescents through participation in life-skills groups - Howe, E. (International Journal of Adolescent Medicine and Health, 1999)
Keywords: adolescence; adolescent; article; attitude; cognitive defect; coping behavior; counseling; dept.swk; ethnic group; female; group psychology; human; human experiment; male; peer-reviewed; problem solving; social behavior; social interaction; social psychology; social status; socialization

Self-help for grandmothers parenting again - Winston, Carole A (Journal of Social Distress and The Homeless, 1999)
Increasingly, grandmothers are parenting grandchildren in homes where parental presence is sporadic or nonexistent. A disproportionate percentage of African American grandparents fall in this category. The author reviews the literature on the African American grandmother in the context of the African American family and describes a practice model for service provision to those women who seek support as they “parent again.”
Keywords: African American; Empowerment model; Parenting grandparents; Support group; dept.swk

Outreach workers' experiences in a homeless outreach project: issues of boundaries, ethics and staff safety - Fisk, Deborah; Rakfeldt, Jaak; Heffernan, Katie; Rowe, Michael (Psychiatric Quarterly, 1999)
Mental health professionals and researchers have emphasized the importance of conducting outreach to locate homeless persons with mental illness, and of creatively engaging these persons into a therapeutic relationship. These outreach and engagement activities raise challenging issues in the areas of client-staff boundaries, professional ethics, and staff safety. While several issues in each of these three key areas have received attention in the growing literature on homelessness, certain issues within each area remain unexplored. The authors draw from the street experiences of outreach staff in a federally funded homeless outreach project to further explore each of these areas, and suggest that experiences of outreach workers are essential in shaping and redefining work activities in these, and other important areas.
Keywords: dept.swk